Nutrição e disponibilidade de nitrogênio no consórcio de milho orgânico com diferentes densidades de fabáceas - Bonfanti, Leila (2019)
The intercropping corn with green manures of the Fabaceae family has been studied as an alternative to supply nitrogen (N), via biological fixation (NBF). Increasing soil organic matter contents and nutrient cycling. However, the Fabaceae species and its density in the intercrop alters the competition patter and demanding studies to optimize the intercrop between Fabaceaes and corn. Therefore, this work aimed to evaluate N availability in the soil, growth, nutritional state and grains yield of corn intercropped with different densities of Crotalaria spectabilis Roth and Cajanus cajan (L.) Millsp in organic system. The study was conducted on crop year of 2017/18, at UFSCar/Araras, SP. Experimental design was of randomized blocks with four repetitions. Treatments consisted of four corn intercrops with: MC5) C. spectabilis - 5 plants.m-1; MG5 C. cajan - 5 plants.m-1; MCG10) C. spectabilis and C. cajan - 10 plants.m-1, five of each species; MCG6) C. spectabilis and C. cajan - 6 plants.m-1, tree of each species, and a lateral control treatment, M) monocultural corn, cultivated distancing six meters from the fabaceas. It was evaluated corn leaf area index (IAF), dry matter (MS) and Falker chlorophyll index (ICF), at phenological stages V4, V8 and VT; leaf micronutrients contents at VT and yield at R6. For the fabaceas, dry mass (MSF) was accessed at corn stages of V4, V8, Vt and R6 and nutrient accumulation at R6. To nitrogen accessible was analyzed by NH4- and NO3- quantification of nifH gene in the soil, at corn phenological stages of V2, V4 and VT. It was observed reduction in grains yield of corn in increases of fabaceas density in intercrops (MCG10), as the pigeon-pea (MG5), because maximized competition interspecific. On the other hand, the intercrop with C. spectabilis (MC5) increased corn dry matter. For the nutritional state the intercrops with fabaceas (MCG6, MG5 and MC5) increases corn phosphorus and potassium leaf content and, increases in fabaceas density in intercrops (MCG10) maximized in nutritional competition, decreases corn phosphorus, potassium and sulfur contents. Not observed increases in corn nitrogen leaf content in presence fabaceas. It nitrogen access in the soil, simultaneous intercropping of C. spectabilis and C. cajan with corn (MCG6) reduces soil contents of ammonium and nitrate but increases corn ICF in comparation others intercrops, indicating nitrogen absorption in the soil by corn plants. Greater fabaceas dry matter amounts increases nifH gene quantity in the soil.